Changes in the structure of financial intermediation: Eastern-Central European developments in the light of global and European trends - András Bethlendi; Katalin Mérő (DANUBE: Law, Economics and Social Issues Review, 2020)
The article analyses the structural changes of the financial intermediary system of Eastern-Central European (ECE) countries, that joined the EU in 2004, namely the Czech Republic, Hungary, Poland, Slovakia and Slovenia (ECE5) in the light of global and European trends from 2004 to 2016. Its two main focuses are the characteristics of the structural shifts and interconnectedness between banks and financial markets, on the one hand, and the size and specificities of shadow banking systems, on the other. Despite the limited catching up of the region the ECE5 countries has a much less deep and more bank-based financial system than their European counterparts without the emergence of significant market-based banking and shadow banking. However, while in the developed countries the most important shadow banking institutions are the non-money market mutual funds, in ECE5 countries other non-bank financial institutions are those that potentially exposed to shadow banking risk.
Keywords: 330; Shadow Banking; Eastern-Central Europe; Market-Based Financial System; Bank-Based Financial System; Financial Structures; Non-bank Financial Intermediation